The Adoption of Mobile Advertisement a Study from Pakistan - Rizwan, Muhammad; Hassan, Mahmood ul; jamil, Nabila; zahra, Rida; rasheed, Rawal; nawaz, Raheeel (Asian Journal of Empirical Research, 2013)
The purpose of our research is to outgrow the usage of mobile phones for advertisement in order to save the time and cost. We believe that in future mobile advertisement will be the best way to communicate and advertised the company’s product directly to target market or target consumer. We have used descriptive research technique to evaluate the acceptability of mobile phone as a medium of advertisement. For that, we have taken a sample of 200 students and used regression analysis technique to measure the effectiveness of our variables influencing mobile advertisement. We have found all of our variables including institutional trust, personal trust, and attitude toward mobile advertisement, purchase intention and permission are having significant and positive relationship with mobile advertisement. All the hypotheses are well supported no one is rejected. We implicate that the relation between these variable with mobile advertisement are positive. These variables like permission, purchase intension are main variable of our topic and also these are important for mobile advertisement. We conclude the result after practical study that mobile advertisement plays a main role to transfer any information regarding news, knowledge, horoscope, tips and any information to the people.